Arbitration as an instrument of support for business transactions - Łukasz Błaszczak (The Central European Review of Economics and Management (CEREM), 2017)
Aim: The article is concerned with the issues relating to arbitration in terms of the development of economy and entrepreneurship. The history of arbitration dates back to ancient times and many of its characteristic features continue to be reflected in the contemporary legal instruments.. The New York Convention on the Recognition and Enforcement of Foreign Arbitral Awards should be distinguished here, along with the European Convention on International Commercial Arbitration. In the context of national arbitration, legal regulations laid down in~ statute provide the main source. Attention should be drawn, in particular,~ to speed as one of its key assets.., In terms of the cost of proceedings, arbitration is less expensive than a court process. The costs of arbitral proceedings appear to be clearly lower than those incurred in the state court proceedings. Another advantage stems from the possibility to design an arbitral procedure. The process of designing the arbitral procedure may proceed according to the arrangement made by the parties themselves. They can decide on the choice of law, arbitrators, their competences and method of conducting a proceeding. This division depends on a number of factors. In the light of the Polish Code of Civil Procedure this division exists only with regard to arbitral awards. The arbitral award is considered to be foreign when it is issued outside Poland. Arbitration resolves disputes which arise between entities participating in business transactions. This function is of relevance from the perspective of the contemporary economic development. Based on the analysis conducted in the paper, the author takes the view that arbitration is of crucial importance to the economic development. A quick dispute resolution has the effect that entrepreneurs show interest in this form of resolving their conflicts. For business transactions, it is paramount to have a prompt dispute resolution between entrepreneurs..Design / Research methods: The interpretation of the impact of arbitration on business transactions was conducted employing historical and dogmatic method. The phenomenon of arbitration has been explained as an alternative form which exists next to mediation proceedings.Conclusions / findings: The studies allow the author to advance a thesis that, apart from the usual economic mechanisms, the mechanisms contributing to the resolution of disputes arising between entrepreneurs ensure the proper functioning of the economy as well. One of such mechanisms is precisely the arbitral tribunal. Unlike common courts, it is a more effective instrument in the hands of entrepreneurs.Originality / value of the article: This article is an example where the links between law and economy are discussed. The economic phenomena have so far been explored solely from the perspective of economics. In this paper, I attempted to show that legal institutions like arbitration in fact serve economic aims. In this sense it is a new approach to the question of business transactions. It can also be evaluated through the prism of economic analysis of law and institutions embedded in law. The topic discussed in the paper is merely a piece of a much broader issue which would require a more in-depth examination. I limit myself only to a certain aspect, yet those issues could be developed into a monograph.
Keywords: K4; 330; arbitration; award; disputes; economy; entrepreneurs; confidentiality; mediation; arbitrator; rules of arbitration